Population genealogy resource shows evidence of familial clustering for Alzheimer disease. (August 2018) - Cannon-Albright, Lisa Anne; Dintelman, Sue; Maness, Tim; Cerny, Johni; Thomas, Alun; Backus, Steven; Farnham, James Michael; Teerlink, Craig Carl; Contreras, Jorge; Kauwe, John S.K.; Meyer, Laurence J.
Abstract : Objective: To show the potential of a resource consisting of a genealogy of the US record linked to National Veterans Health Administration (VHA) patient data for investigation of the genetic contribution to health-related phenotypes, we present an analysis of familial clustering of VHA patients diagnosed with Alzheimer disease (AD). Methods: Patients with AD were identified by the International Classification of Diseases code. The Genealogical Index of Familiality method was used to compare the average relatedness of VHA patients with AD with expected relatedness. Relative risks for AD were estimated in first- to fifth- degree relatives of patients with AD using population rates for AD. Results: Evidence for significant excess relatedness and significantly elevated risks for AD in relatives was observed; multiple pedigrees with a significant excess of VHA patients with AD were identified. Conclusions: This analysis of AD shows the nascent power of the US Veterans Genealogy Resource, in early stages, to provide evidence for familial clustering of multiple phenotypes, and shows the utility of this VHA genealogic resource for future genetic studies.